2017
DOI: 10.1038/s41598-017-18242-9
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Cell Membrane Component Domains in Artificial Lipid Bilayer

Abstract: The lipid bilayer environment around membrane proteins strongly affects their structure and functions. Here, we aimed to study the fusion of proteoliposomes (PLs) derived from cultured cells with an artificial lipid bilayer membrane and the distribution of the PL components after the fusion. PLs, which were extracted as a crude membrane fraction from Chinese hamster ovary (CHO) cells, formed isolated domains in a supported lipid bilayer (SLB), comprising phosphatidylcholine (PC), phosphatidylethanolamine (PE),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 38 publications
4
33
0
Order By: Relevance
“…Cellular lipid composition has been considered as cellular dynamic. Lipid is a building block of cell membrane which involved in many cellular processes such as cell signaling, cellular transportation leading to form lipid domain . Lipid accumulation has recently been reported that induced cell death via apoptosis and established TKIs resistance on NSCLC cell line and patient tissues .…”
Section: Discussionmentioning
confidence: 99%
“…Cellular lipid composition has been considered as cellular dynamic. Lipid is a building block of cell membrane which involved in many cellular processes such as cell signaling, cellular transportation leading to form lipid domain . Lipid accumulation has recently been reported that induced cell death via apoptosis and established TKIs resistance on NSCLC cell line and patient tissues .…”
Section: Discussionmentioning
confidence: 99%
“…When the substrate was incubated in the PLE-suspension with [Ca 2+ ] = 2 mM, a circular region with a uniform fluorescence intensity existed ( Figure 1B). The fluorescence intensity shows that single layer of SLB was formed in this region (Tero et al, 2017;Kakimoto et al, 2018). The surrounding gray region contained bright dots that had similar fluorescence intensity to the circular SLB region (Figure 1B, inset).…”
Section: Methodsmentioning
confidence: 85%
“…They are used to investigate the fundamental physicochemical properties and molecular distribution of lipid bilayers with atomic force microscopy (AFM) and fluorescence-microscope-based methods (El Kirat et al, 2010;Tero, 2012;Zhong and He, 2012). Morphology and physicochemical properties of lipid domains, and shape transformation of membranes have been studied in multicomponent SLBs (El Kirat et al, 2010;Goertz et al, 2011;Zhong and He, 2012;Kawakami et al, 2017;Sumitomo and Oshima, 2017;Tero et al, 2017;Kakimoto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…XAS can be applied to the investigation of several catalytic and electrochemical reactions such as Li K-edge XAS of the lithium ion battery (Thackeray, 1997), S L-edge XAS of Nafion polymer films in a fuel cell electrode (Masuda et al, 2013) and B Kedge XAS of the nickel borate electrocatalyst for oxygen evolution reactions (Dincȃ et al, 2010). The application of biological phenomena is also expected, such as molecular interactions of phosphate ions with water in liquid bilayers around biological membranes (Tero et al, 2017) from P L-edge XAS. Consequently, XAS in the low-energy region has the potential to enhance our understanding of physical, chemical and biological phenomena in solution, which would be realized by the argon gas window.…”
Section: Discussionmentioning
confidence: 99%